Dependence of the foaming window of poly(ethylene terephthalate-co-ethylene 2, 5-furandicarboxylate) copolyesters on FDCA content. (21st July 2022) - Wang, Zhijun; Wang, Jinggang; Pang, Yongyan; Zhu, Jin; Zheng, Wenge
Abstract: The objective of the present work was to study the dependence of the foaming temperature window of poly(ethylene terephthalate- co -ethylene 2, 5-furandicarboxylate) (PEFT) copolyesters on 2, 5-furandicarboxylic acid (FDCA) content after different saturation pressures. First, the chemical structure of PEFT copolyesters was characterized, and the effect of FDCA content on the sorption of carbon dioxide (CO2 ) and the crystallization behavior of PEFT copolyesters was studied. Second, the foaming of PEFT copolyesters was carried out using a batch foaming process. Third, the foaming temperature window was defined for PEFT copolyesters through identifying the lower and the upper foaming temperature boundaries. It was found that with the increase of FDCA content, the sorption of CO2 decreased, and the melting temperature and the crystallinity of PEFT decreased. This led to the increase of the lower foaming temperature while the decrease of the upper one, thus making the foaming temperature window gradually narrowed. It is considered that the lower foaming temperature was determined by the rigidity of the macromolecular chains as well as the CO2 sorption, while the upper one by the crystals formed in PEFT with copolymerization of FDCA units. In addition, with the increase of the saturation pressure, the lower foaming temperature of all PEFT samples decreased, and the upper foaming temperature of PEFT15%, PEFT20% and PEFT30% decreased as well, attributed to the plasticization effect of CO2 . However, the upper foaming temperature of PET, PEFT5% and PEFT10% unexpectedly increased with the saturation pressure due to the CO2 -induced crystallization. The findings in this study are very important for guiding the foaming and cell structure control, not only for PEFT copolyesters, but also for other semicrystalline copolymers. Graphical abstract: Image 1 Highlights: Sorption of CO2, melting temperature and crystallinity of PEFT decrease with FDCA. Lower and upper foaming temperature increases and decreases with FDCA, respectively. Foaming temperature window of PEFT turns gradually narrowed with FDCA. Lower foaming temperature of PEFT decreases with saturation pressure. Change of upper foaming temperature with saturation pressure depends on FDCA.